Maximizing underwater energy harvesting efficiency using flexible solar cells: A pathway to sustainable ocean power - Haoliang Bai; Tonghui Lu; Wenzhuo Liu; Xianglin Li; Wenhao Lv; Song Lv (Proceedings of the National Academy of Sciences, 2025)
Photovoltaic technology has emerged as a key candidate for powering underwater devices. However, traditional solar cells face limitations in real marine environments. Flexible solar cells offer new possibilities for underwater energy harvesting. This study identifies the optimal bandgap and depth for flexible underwater solar cells through detailed balance calculations and experiments. We also established an optical model for underwater flexible solar cells, determining the ideal curvature through outdoor testing. The flexible a-Si solar cell achieves an impressive maximum efficiency of 59.7% at 2 m, generating up to 15.9% more energy throughout the day compared to planar solar cells. Theoretical results surpass the fundamental limits of seabed solar collection, outperforming all existing underwater photovoltaic solutions. Building on this foundation, we demonstrated their all-day capabilities in powering unmanned underwater vehicles (UUVs) and LED light beacons. Furthermore, we explored the global power generation potential of flexible solar cells at typical depths, identifying the optimal operating ranges during different seasons and analyzing the power generation costs for typical water bodies. This study highlights the immense potential of flexible solar cells in advancing marine energy generation.